PENGARUH ENTREPRENEURIAL LEADERSHIP TERHADAP PRODUCT INNOVATION PADA INDUSTRI MAKANAN DI YOGYAKARTA - Dwi Wahyu Pril Ranto (Jurnal Bisnis, Manajemen, dan Akuntansi, 2017)
This study aims to examine the influence of Entrepreneurial Leadership which consists ofthe dimensions of Able to Motivate, Visionary, Proactive, Innovative, Risk Taking, AchievementOriented, Persistence partially and simultaneously to product innovation.The population in this study is the SMEs engaged in food in the city of Yogyakarta. Thesampling technique is used purposive sampling with the sample criteria that is the owners of SMEsor managers who have 1 (one) year running its business, because it is considered the entrepreneursof UMKM have been able to survive and run their business well. In addition, this study also usesconvenience sampling technique that is sampling because of the convenience factor.Data analysis tool used in this research is multiple regression analysis. Based on theresults of the research, it is found that the dimensions of Entrepreneurial Leadership consisting ofdimensions of Able to Motivate, Visionary, Proactive, Innovative, Risk Taking, AchievementOriented, Persistence partially and simultaneously have influence on product innovation.Kata kunci:Entrepreneurial Leadership, Able to Motivate, Visionary, Proactive,innovativeness